Perception of Communication Competence, Self-efficacy, and Audience Response to Public Speaking Anxiety in Professional Psychology Students - Bawinda S Lestari; Joniarto Parung; Frikson C Sinambela (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Anxiety in public speaking is a form of worry caused by a wrong mindset towards his or herself and also of the audience's response. The study aimed to examine the role of self-efficacy, perception of communication competence, and audience response to public speaking anxiety. The study subjects were 533 professional psychology students. The data is collected online and analyzed using a double linear regression technique. The results showed that perceptions of communication competence and self-efficacy together affected public speaking anxiety. Perceptions of communication competence have the greatest influence on public speaking anxiety. The audience's response does not affect the anxiety of speaking in general in professional psychology students. Based on this research, professional psychology education providers need to involve learning programs that can improve the perception of communication competence and self-efficacy in professional psychology students to help reduce public speaking anxiety.